Extraction and separation of rare earth elements from hydrothermal metalliferous sediments. (15th March 2018) - Josso, Pierre; Roberts, Steve; Teagle, Damon A.H.; Pourret, Olivier; Herrington, Richard; Ponce de Leon Albarran, Carlos
Graphical abstract: Optimized workflow of metalliferous sediment processing for the extraction of REY by simple acid leaching and oxalate precipitation for the production of a rare earth oxide concentrate. Highlights: Umbers are low grade REY ferromanganese ore with low radioactive content. 92% REY recovery in simple leaching experiment using optimal leaching parameters. REY precipitation and purity as an oxalate cake is strongly pH dependent. REY distribution trends in oxalate precipitate is explained using chemical modelling. A two-step process recovers >85% of initial REY content at 65% precipitate purity. Abstract: Rare earth elements (REE) can be efficiently extracted from umbers, ferromanganese metalliferous sediments of the Troodos ophiolite (Cyprus) by simple leaching and selective precipitation, without accumulation of radioactive by-products. Umbers are dominantly composed of amorphous Fe and Mn oxides with minor goethite, quartz and zeolites, and contain 350–500 mg  kg −1 of rare earth elements and yttrium (REY), 200 times lower than many of the major REY source ores. To compensate for relatively low grades, a cost-effective extraction process was developed that utilises a weak lixiviant concentration (0.1–1.5 N) and short reaction times (5 min to 11 h). Acid solutions recover 70–85% of the initial sample REY content even at 20 °C. By contrast, extraction using ionic solutions of NaCl and ammonium sulphate proved ineffective. Acid recoveries of REY increase by nearly 10% at 70 °C and the use of different acids (HCl, HNO3, H2 SO4 ) yields comparable results. The main impurities in the leachate include Ca and Na at even the weakest acid concentration (0.1 N). However, two-step leaching method greatly reduces concentrations of impurities in the REY-rich liquor, although with REY losses approaching 20%. Purification of the leach liquor via selective precipitation of REY as an oxalate is highly efficient although pH dependent. With maximum REY precipitation (96–99%) occurring between pH 1 and 2, the precise adjustment of pH allows separation of REY from other precipitating impurities (Ca). The maximum purity of the precipitate is achieved at pH 1.1 (>65%). Strong and consistent fractionation along the lanthanide series observed during the precipitation experiments has been successfully explained using a speciation modelling software (PHREEQC). The uptake of REY by oxalate in the experiments closely follows the bell-shape distribution of REY-oxalate solid complexes stability constant (−log β (RE2 Ox3 ·nH2 O)) replicating the fractionation trends observed at pH < 1.1. In addition, the modelling demonstrates that at equivalent REE concentration in solution, oxalate precipitates fractionate REY in the following order: middle REE > light REE ≫ heavy REE. This ordering and the variable degrees of uptake reflects the interplay of aqueous REY-oxalate complexes (logHOx β1, Ox β1 andOx β2 ) with the natural fractionation induced by solid REY-oxalate stability constant distribution. Overall, the combined leaching process and selective oxalate precipitation produces a total enrichment factor ranging between 1400 and 2400 for REY from the sample to the oxalate precipitate in a simple two-step process forming a high-purity end-product of mixed REY.